Pethia poiensis, a new species of cyprinid fish from the Chindwin Basin of Manipur, India - Shangningam, Bungdon; Vishwanath, Waikhom (Zootaxa, 2018)
Pethia poiensis, a new cyprinid species, is described from the Challou River, Chindwin Basin, Manipur, India. The new species is characterised by an incomplete lateral line with 7–9 pored scales, the absence of barbels, 19–20 scales in lateral series, 9–10 pre-dorsal scales, 18 pre-anal scales, 3½ scales between dorsal-fin origin and lateral line, three scales between lateral line and pelvic-fin origin and a unique colour pattern consisting of a humeral spot encompassing the third and fourth lateral-line scales, a caudal spot on the 16th and 17th lateral series scales and a black stripe along the flank. A revised key to the species of Pethia found in the Chindwin-Irrawaddy drainage is presented.